Electrically Tunable and Dramatically Enhanced Valley‐Polarized Emission of Monolayer WS2 at Room Temperature with Plasmonic Archimedes Spiral Nanostructures. Issue 3 (28th November 2021) - Lin, Wei‐Hsiang; Wu, Pin Chieh; Akbari, Hamidreza; Rossman, George R.; Yeh, Nai‐Chang; Atwater, Harry A.
Abstract: Monolayer transition metal dichalcogenides (TMDs) have intrinsic valley degrees of freedom, making them appealing for exploiting valleytronic applications in information storage and processing. WS2 monolayer possesses two inequivalent valleys in the Brillouin zone, each valley coupling selectively with a circular polarization of light. The degree of valley polarization (DVP) under the excitation of circularly polarized light (CPL) is a parameter that determines the purity of valley polarized photoluminescence (PL) of monolayer WS2 . Here efficient tailoring of valley‐polarized PL from monolayer WS2 at room temperature (RT) through surface plasmon–exciton interactions with plasmonic Archimedes spiral (PAS) nanostructures is reported. The DVP of WS2 at RT can be enhanced from <5% to 40% and 50% by using 2 turns (2T) and 4 turns (4T) of PAS, respectively. Further enhancement and control of excitonic valley polarization is demonstrated by electrostatically doping monolayer WS2 . For CPL on WS2 –2TPAS heterostructures, the 40% valley polarization is enhanced to 70% by modulating the carrier doping via a backgate, which may be attributed to the screening of momentum‐dependent long‐range electron–hole exchange interactions. The manifestation of electrically tunable valley‐polarized emission from WS2 –PAS heterostructures presents a new strategy toward harnessing valley excitons for application in ultrathin valleytronic devices. Abstract : Efficient tailoring of valley‐polarized photoluminescence from monolayer WS2 at room temperature (RT) through surface plasmon–exciton interactions with plasmonic Archimedes spiral (PAS) nanostructures is achieved in this manuscript. The degree of valley polarization of WS2 –PAS heterostructures at RT can be further enhanced from 40% to 70% by modulating the carrier doping via a backgate field effect transistor (FET) device.